Environmental concerns in international investment treaty arbitration - Carvalho, Rita Correia de (2022)
In recent years, more than 3000 + international law instruments adopt investment treaty arbitration as their dispute settlement mechanism. However, these instruments have been criticized for interfering with the right of sovereign states to regulate. For this and other reasons, the international arena has reflected upon the suitability of such disputes related to environmental concerns being settled through investment treaty arbitration. This dissertation pursues the objective of exploring possible outcomes of this discussion, through an analysis of both regimes: international investment treaty arbitration law and environmental law.